Keefektifan Model Pembelajaran Tipe Think Pair Share terhadap Prestasi Belajar Matematika Ditinjau dari Self Efficacy Siswa - Nuning Melianingsih; Desi Tri Utami (SAP (Susunan Artikel Pendidikan), 2019)
This research is aimed to know: (1) Which learning did give better mathematical achievement, cooperative learning which is typed Think Pair Share (TPS) or conventional learning. (2) Did the students with higher self efficacy have better learning achievement in mathematics than the students don’t. (3) Are there any differences in learning achievement in mathematics from the students with higher self efficacy and the students with lower self efficacy in TPS learning model and conventional learning model. This research is quasi-experimental. The populations are all  students grade X mechanical automotive in Sukoharjo region. The technique of data analysis used is test analysis variation two ways with unequal cells. The conclusions are that: (1) TPS learning model produced better learning achiement than conventional model; (2) there are any differences learning achievement in mathematics from the sudents that have higher self efficacy, averege self efficacy and lower self efficacy; (3) There is no interaction between learning model with the students’ sefl efficacy toward learning achievement in mathematics.